Case Series of Repetitive Transcranial Magnetic Stimulation in Treatment-Resistant Depression - Gue, Kay Lyn; Ting, Chuong Hock (FAKULTI PERUBATAN DAN SAINS KESIHATAN, UPM, 2024)
Introduction: Repetitive transcranial magnetic stimulation (rTMS) is a non-invasive form of brain stimulation therapy and The United States Food and Drug Administration (FDA) approved the use of rTMS for the treatment of major depressive disorder (MDD) in 2008. Meta-analyses have shown that patients with treatment-resistant depression (TRD) showed clinically significant improvement after treatment with rTMS but studies on the efficacy of rTMS in special populations such as the elderly are still very limited. Case Series: This case series aimed to report the efficacy of rTMS on treatment-resistant depression in patients of diverse ages in Hospital Sentosa Kuching, Malaysia. Four patients with treatment-resistant depression, aged 17 to 73 years old, completed the course of rTMS. All patients received 20 sessions of rTMS, with 120% motor threshold, 10 Hz rTMS, 3000 pulses per session, and five times per week. The outcome of treatment was measured using The Montgomery–Åsberg Depression Rating Scale (MADRS) and responders were defined as having ≥ 50% reduction in score. Conclusion: Two patients responded to the treatment and two elderly patients did not respond to the rTMS treatment, but it was well tolerated by all patients. rTMS can be a promising treatment option for TRD and more research may be needed to determine the most effective treatment protocol.